Value of acute neurovascular imaging in patients with suspected transient ischemic attack. Issue 154 (September 2022) - Jalilianhasanpour, Rozita; Huntley, Joseph H.; Alvin, Matthew D.; Hause, Stephanie; Ali, Nabila; Urrutia, Victor; Ghazi Sherbaf, Farzaneh; Johnson, Pamela T.; Yousem, David M.; Yedavalli, Vivek
Highlights: Of 398 patients presenting to the emergency department with transient neurologic deficits, 28.1% were ultimately diagnosed with a true TIA, but over 84% underwent ED neurovascular imaging. Of those undergoing neurovascular imaging, 10.5% showed > 50% intracranial vascular stenosis and 1.7% showed > 70% cervical carotid artery stenosis. In those patients who were DWI negative for strokes, the rate of intracranial stenosis dropped to 7.8% and to 0.9% in the neck versus 24.4% and 2.4% respectively if the DWI scan was positive. Risk factors for significant stenoses after multivariate linear regression analysis were DWI positivity in the neck, and black race, hypertension and DWI positivity intracranially. A follow-up stroke within 90 days was equally likely in true TIA patients with or without severe vascular stenosis. Abstract: Purpose: Acute neurovascular imaging including MRA and/or CTA are routinely performed in the emergency departments (ED) for patients who present with suspected transient ischemic attacks (TIA). Given the current emphasis on mitigating the rising cost of health care nationally, and promoting high value practice, we sought to determine 1) the value of acute neurovascular imaging in patients presenting to the ED with TIA-like symptoms, and 2) whether these neurovascular studies led to a difference in management strategies. Method: We retrospectively reviewed 398 ED patients who presented with transient neurological deficits and underwent neurovascular imaging from 2015 to 2018. We reviewed diffusion weighted imaging (DWI) and neurovascular results by patient demographics, baseline risk factors, final diagnosis, treatment/management dispositions and three-month follow-up. Results: 28.1% (112/398) of patients were diagnosed with true TIA, whereas 71.9% patients were deemed to have a non-vascular etiology. Total rates of positive MRA/CTA for severe intracranial (>50%) and cervical vessel (>70%) stenosis were 10.5% and 1.7%. Patients with positive DWI scans had significantly higher rates of severe vascular stenosis (24.4% versus 7.8% intracranially and 2.4% versus 0.9% in the neck) compared to those with negative DWI scans. All patients were treated with multi-pronged medical therapies with no immediate surgical intervention. A follow-up stroke was equally likely in TIA patients with or without severe vascular stenosis. Conclusions: In patients presenting with TIA-like symptoms and DWI negative scans, the overall rate of positive neurovascular studies is very low. Triaging with DWI can reduce the frequency of unnecessary neurovascular imaging.